The fighter [videorecording (DVD)] - Russell, David O., 1958-; Wahlberg, Mark, 1971-; Bale, Christian, 1974-; Adams, Amy; Leo, Melissa (Paramount Home Entertainment, 2011)
Micky Ward is a struggling boxer long overshadowed by his older brother and trainer, Dicky, a local legend battling his own demons. Their explosive relationship threatens to take them both down. However, the bond of blood may be their only chance to redeem their pasts, and, at last, give their hard-luck town what it's been waiting for: pride.